1984
DOI: 10.1007/bf00542146
|View full text |Cite
|
Sign up to set email alerts
|

Lack of clinically important interaction between erythromycin and theophylline

Abstract: In 11 healthy volunteers the kinetics of theophylline and the plasma levels and the urinary excretion of its metabolites were studied before and after treatment with erythromycin for 10 days. Theophylline was administered as an intravenous bolus injection (280 mg) followed by a constant intravenous infusion (23.8 +/- 4.1 mg/h) for 6 hours. The total clearance of theophylline at steady-state (63.4 +/- 9.9 vs 63.8 +/- 14.4 ml/min, before vs after erythromycin treatment) and the elimination half-life after cessat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…After discontinuation of erythromycin she was able to resume her routine bronchodilator therapy. A recent study by Hildebrandt et al (1984) in 11 volunteers found that the kinetics of theophylline and its metabolites were unchanged by administration of erythromycin stearate 250mg 4 times daily for 10 days. Theophylline was administered as a 280mg intravenous bolus followed by a constant rate infusion (23.8 ± 4.1 mg/h) for 6 hours before and after the 10-day erythromycin administration.…”
Section: Erythromycinmentioning
confidence: 96%
“…After discontinuation of erythromycin she was able to resume her routine bronchodilator therapy. A recent study by Hildebrandt et al (1984) in 11 volunteers found that the kinetics of theophylline and its metabolites were unchanged by administration of erythromycin stearate 250mg 4 times daily for 10 days. Theophylline was administered as a 280mg intravenous bolus followed by a constant rate infusion (23.8 ± 4.1 mg/h) for 6 hours before and after the 10-day erythromycin administration.…”
Section: Erythromycinmentioning
confidence: 96%